An Econometric Analysis on Selected Socioeconomic Indicators: Evidence from State of Malacca, Malaysia - Rosilawati Amiruddin; Ismadi Ismail; D., Agus Harjito; Wahyu Ario Pratomo (Universitas Islam Indonesia, 2007)
In attaining a sustainable economic growth, the government or the relevant au-thorities must not disregard social life of the society. Economic development must coincide with the social development of the society. This study will endeavor to investigate the socio-economic level of household in the state of Malacca by gathering information on 334 house-holds located in the District of Alor Gajah. The main objective of this study is to view the socioeconomic level for selected indicators such as income, education and health. The method of this study is by the issuance of questionnaires which conform to the needs of this study. The methodology employed in analyzing the data obtained is through descriptive analysis and econometric techniques especially in examining the relationship between social and economic variables.The result of the study shows that the Malay households control the income in the district and have a higher educational level compared to other ethnics relatively. The cost of education for household depends on the income level, the members in the household which are still studying and the ethnicity. The district’s households still prefer to obtain health ser-vices provided by the government and the degree of dependency decreased accordingly with an increase in income. Although, this study is limited to only few socioeconomic indicators, it still can be considered as an initial step for further studies to be made on socio economy in the state of Malacca.Keywords: socioeconomics, household, econometric analysis.